2013
DOI: 10.1111/hepr.12243
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell hepatitis induced by the termination of antiviral therapy for recurrent hepatitis C after living donor liver transplantation

Abstract: Plasma cell hepatitis (PCH) is an idiopathic disorder characterized by plasma cell infiltration in the allografts of patients who have undergone liver transplantation. Although an increasing number of cases of PCH have been reported in liver transplant recipients with hepatitis C recurrence treated with interferon, it is unclear whether PCH is induced by interferon itself. Here, we describe the cases of two patients who developed PCH just after the termination of antiviral therapy for recurrent hepatitis C aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, IFN‐mediated graft dysfunction is a significant clinical problem that warrants particular caution following living donor LT . Moreover, it was reported that IFN‐based antiviral therapy for recurrent hepatitis C after living donor LT had the potential for causing plasma cell hepatitis and chronic rejection . Therefore, for such difficult‐to‐treat post‐LT patients, IFN‐free daclatasvir and asunaprevir combination therapy will likely be a standard therapy …”
Section: Discussionmentioning
confidence: 99%
“…However, IFN‐mediated graft dysfunction is a significant clinical problem that warrants particular caution following living donor LT . Moreover, it was reported that IFN‐based antiviral therapy for recurrent hepatitis C after living donor LT had the potential for causing plasma cell hepatitis and chronic rejection . Therefore, for such difficult‐to‐treat post‐LT patients, IFN‐free daclatasvir and asunaprevir combination therapy will likely be a standard therapy …”
Section: Discussionmentioning
confidence: 99%
“…In five patients, rejection progressed rapidly and resulted in death within 3 months after diagnosis . On the other hand, plasma cell hepatitis induced by antiviral therapy for recurrent hepatitis C after LDLT . Although it is important that SVR induced by IFN therapy improved survival rate in patients with recurrent post‐LDLT HCV infection, IFN therapy may be recommended in these patients while we are careful of chronic rejection and plasma cell hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there have been several publications regarding de novo hepatitis during or after interferon-based anti-HCV treatment for recurrent hepatitis C posttransplantation (67)(68)(69). However, its pathophysiology is still uncertain, and it is still controversial whether de novo AIH represents a specific type of rejection or a form of have reported recurrent AIH posttransplantation (8,32), since the first report by Neuberger et al in 1984 (33).…”
Section: De-novo Autoimmune Hepatitismentioning
confidence: 99%